Food web models reveal potential ecosystem effects of seagrass recovery in the northern Wadden Sea. (20th December 2020) - Horn, Sabine; Coll, Marta; Asmus, Harald; Dolch, Tobias
Abstract : In contrast to the global trend, seagrass beds have recovered in size and density in the northern part of the European Wadden Sea, but ecosystem effects of seagrass recovery and the impacts to ecosystem services are largely unknown. We used temporal‐dynamic food web modeling Ecopath with Ecosim to assess potential ecosystem effects of seagrass recovery in the semi‐enclosed Sylt‐Rømø Bight at the German‐Danish border. In addition to changes in the system's structure and functioning over time, the model predicted changes in biomass of seagrass‐associated species. For seagrass consumers, we projected an increase in biomass as a result of an increase in food supply. Likewise, the model predicted an increase in biomass of seagrass meadow inhabitants from decreased predation pressure. Correspondingly, the main predators of these inhabitants decreased in biomass according to model results. Proxies representing ecosystem services predicted an increase of tourism appeal of the site with increasing seagrass meadows. Indirect mediation effects of seagrass severely influenced the model output and are thus crucial to forecast potential effects of the recovery of habitat‐forming species. Our study illustrates that holistic approaches such as food web models could provide a suitable basis for predicting ecosystem effects of changes in the biomass of habitat‐forming species such as seagrasses.